PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS DI SMA NEGERI 1 MERLUNG - Nur Alima, Benar Sembiring (Universitas Batanghari Jambi, 2020)
Abstract This study aims to determine the description and influence of discipline on student learning outcomes in economics class X social studies at SMA Negeri 1 Merlung. The method used in this research is descriptive method with quantitative approach. The results of the study explained that: 1) Based on the calculation of the learning discipline known Mean is 124.16. The median is 127.00 and mode is 127. While the mean learning outcome calculation is 80.93. The median is 80.00 and the mode is 80. 2) Based on data processing through simple regression analysis obtained information that the discipline of learning has a significant effect on student learning outcomes in Economics subjects class X IPS in SMA Negeri 1 Merlung. This is indicated by the value of Sig. < 0.05, which is 0,000 < 0.05. In addition, the results of hypothesis testing also informs that learning facilities have a significant effect on student learning outcomes in Economics X social class subjects in SMA Negeri 1 Merlung, which is indicated by the value of tcount> ttable. Keywords: Learning Discipline, Learning Outcomes